Situasi Filariasis Di Kabupaten Tabalong-Kalimantan Selatan Tahun 1999-2009 - Anorital, Anorital (Central Basic Biomedical and Health Technology, 2012)
Tabalong Regency represents one of filariasis endemic area in South Kalimantan Province. Endemicity of filariasis in Tabalong is identified from finger blood survey and clinical symptom of filariasis (i.e. lymphadenitis and retrograde lymphangitis) among the residents in 28 villages. This article discusses the situation of filariasis in the district of Tabalong during the period 1999-2009.This article compiled by collecting information and secondary data derived from Tabalong District Health Office annual reports of filariasis research and finger blood surveys ever carried out in Tabalong District. Finger blood survey results conducted in 28 villages from 1999-2009 showed microfilaria rate above 1% (between 1,9-4,7%). With this finding, filariasis elimination program with mass treatment has been done since 2004, carried out gradually to all the residents in the district Tabalong. Until 2009 treatment coverage was about 79.2% and approximately 0.2- 6.7% of the population experienced post-treatment follow-up events. It is recommended to increasing operational costs for mass treatment funded from local budget and involvement of NGOs in order to increase mass treatment coverage including patient education and counseling to overwhelm post-treatment follow-up events.Key words: lymphatic filariasis, filariasis Mass-treatmentÂ Abstrak Kabupaten Tabalong merupakan salah satu daerah endemis filariasis di Provinsi Kalimantan Selatan. Endemisitas filariasis di Tabalong diketahui dari hasil survei darah jari dan gejala klinis (yaitu limfadenitis dan pembengkakan kelenjar limfa) diantara para penduduk di 28 desa. Artikel ini menjelaskan tentang situasi filariasis di Kabupaten Tabalong selama periode 1999-2009. Artikel ini merupakan kompilasi data sekunder dan laporan hasil penelitian filariasis yang pernah dilaksanakan di Kabupaten Tabalong. Hasil survei darah jari yang dilaksanakan di 28 desa dari tahun 1999-2009 memperlihatkan angka mikrofilaria di atas 1% (antara 1,9-4,7%). Program eliminasi filariasis dengan pengobatan massal dilaksanakan sejak tahun 2004 pada seluruh wilayah di Kabupaten Tabalong. Sejak tahun 2009 cakupan pengobatan massal sebesar 79,2% dan 0,2-6,7% dari penduduk mengalami kejadian ikutan pasca pengobatan massal. Direkomendasikan agar biaya operasional pengobatan massal ditingkatkan jumlahnya dan keterlibatan LSM untuk meningkatkan cakupan pengobatan massal meliputi penyuluhan dan pendampingan kepada penduduk untuk penanggulangan kejadian ikutan pasca pengobatan agar tidak menimbulkan efek jera.Kata kunci: limfatik filariasis, pengobatan massal filariasis.